The 'border' in the New Global Economic Geography: the cases of Mexico and Morocco - Navarro Martínez, Juan; Soriano Miras, Rosa María; Trinidad Requena, Antonio (Papeles de Europa, 2023)
From a comparative perspective, this article analyzes the new dynamics of industrial relocation in Mexico and Morocco, using as a theoretical framework the Theory of the Localized Global Economy (TLGE) and as an analytical framework the Industrial Relocation Index (IRI), both formulated by Trinidad et al. (2015). The IRI (as a theoretical model) provides insight into the most advantageous locations for transnational companies in their strategies to achieve the "successful product" with the least possible uncertainty. To this end, it takes into account the five dimensions that make it up: product, workers, legitimacy, distance and demand. It is observed how the global economy is located, among others, in two border regions: Tijuana (Mexico) and Tangier-Tetouan (Morocco) due to their geostrategic location between the places of production and the places of consumption.
Keywords: Industrial relocation; Global economy; Border; Mexico; Morocco